Performance and design of reinforced slopes considering regional hydrological conditions. Issue 5 (14th August 2019) - Yang, K-H; Nguyen, T. S.; Li, Y-H; Leshchinsky, B.
Abstract : This study presents a series of numerical analyses investigating the impact of rainfall on the performance and design of geosynthetic-reinforced soil slopes (RSSs). The importance of considering regional hydrological conditions for designs of RSSs, particularly when marginal soil is used as backfill, is demonstrated and highlighted. RSSs with backfills containing five different fines contents subjected to various combinations of initial hydraulic conditions and major rainfall events were modeled. The input rainfall was determined from the rainfall intensity–duration–frequency (I–D–F) curves to realistically account for the impact of regional hydrological conditions. The hydraulic responses and stability of the RSSs including their porewater pressure development and factor of safety were then evaluated and compared. The results revealed that the applied rainfall scenarios had little influence on the performance of RSSs with high-quality backfills (i.e. backfill with low fines content), whereas those with prolonged rainfall duration substantially affected the performance of RSSs with high fines content backfills. Rainfall thresholds were established for the RSSs with various backfills and initial conditions and compared with the regional I–D–F curves to provide a simplified and robust method for facilitating backfill selection and assessing the failure risk of RSSs.